Pubertal Onset in Apparently Healthy Indian Boys and Impact of Obesity - Surana, Vineet (Indian J Endocrinol Metab, 2017)
OBJECTIVE: Primary – to determine the age of pubertal onset in Indian boys. Secondary – (a) to assess the impact of obesity on pubertal timing, (b) to assess the relationship between gonadotropins and puberty. DESIGN: Cross-sectional. SETTING: General community-seven schools across New Delhi. PARTICIPANTS: Random sample of 1306 school boys, aged 6–17 years. MATERIALS AND METHODS: Anthropometric measurement for weight and height and pubertal staging was performed for all subjects. Body mass index (BMI) was calculated to define overweight/obesity. Serum luteinizing hormone (LH), follicle stimulating hormone, and serum testosterone were measured in every sixth subject. MAIN OUTCOME MEASURE: Age at pubertal onset-testicular volume ≥4 mL (gonadarche) and pubic hair Stage II. RESULTS: Median age of attaining gonadarche and pubarche was 10.41 years (95% confidence interval [CI]: 10.2–10.6 years) and 13.60 (95% CI: 13.3–14.0 years), respectively. No significant difference in the age of attainment of gonadarche was observed in boys with normal or raised BMI, though pubarche occurred 8 months earlier in the latter group. Serum gonadotropins and testosterone increased with increasing stages of puberty but were unaffected by BMI. Serum LH level of 1.02 mIU/mL and testosterone level of >0.14 ng/mL showed the best prediction for pubertal onset. CONCLUSION: The study establishes a secular trend of the age of onset of puberty in Indian boys. Pubarche occurred earlier in overweight/obese boys. The cutoff levels of serum LH and testosterone for prediction of pubertal onset have been established.